Assessment of Effect of Clay Mineral Application on Establishment of Guava under Semi-arid Alfisols - Rao, V.S.; Sankar, G.R. Maruthi (Indian Journal of Agroforestry, 2020)
The effects of clay mineral application on different soil, plant growth and physiological parameters in guava have been examined in this paper. Among different leveis of clay mineral tested, application of 5.6 kg/pit of clay mineral were found to be highly effective and efficient compared to either control, 2.8 kg/pit or 11.2 kg/pit for different soil and plant parameters studied. The estimates of correlation between tree height, number of branches, spread in East-West and North-South directions, girth, stomatal conductance, relative water content, canopy temperature, soil moisture at field capacity and permanent wilting point, gravimetrically measured soil moisture (0-15 cm and 15-30 cm depth) and number of fruits in guava indicated that height was significantly correlated with number of branches, North-South spread, East-West spread, girth and soil moisture (field capacity and permanent wilting point). Significant correlations were also found for the number of branches with soil moisture (field capacity and permanent wilting point). Further, North-South and East-West spread had a significant correlation with girth. Stomatal conductance and relative water content were also significantly correlated in the establishment of guava. Regression models of height and number of branches through days after planting were calibrated under each of the 4 treatments of clay mineral application. It was observed that predictability was higher when 5.6 kg/pit of clay mineral was applied and was efficient for improving height and number of branches of guava compared to either 2.8 or 11.2 kg/pit of clay mineral application. The study indicated that clay mineral application was highly beneficial for establishment of guava in semi-arid alfisols under dryland conditions.